Some problems with the interaction of old and new knowledge - Vaitkevičius, J. (Psichologija, 1962)
The interoperability of old and new knowledge in the learning process is very important; it’s an established issue in pedagogical literature. However, in the classical pedagogy this issue was discussed unilaterally: the old knowledge was regarded only as a way to more easily assimilate new knowledge (from the known to the unknown), excluding all possible interaction of old and new knowledge, which should be what determines the nature of learning and analyzing the new material. No attention was paid to the flip side either, the development of old knowledge under new conditions to aid new knowledge. This point of view dominates pedagogical and psychological literature to this day. Also, often the interaction of old and new knowledge is considered narrowly, only within one subject, within the range of a single class. Our research has shown that interaction between new and old knowledge goes a long way in combining the learning process into a single system. We found close links in what students learn in science lessons: 5th grade botanics, 7th grade physics, and 8th grade chemistry. This similar software acquired in our aforementioned subjects, basically determines the mental activity students perform by systemizing knowledge. This led us to the conclusion that students’ mental development is very important for excellence in all subjects, not an individual subject, because one subject is based on knowledge acquired in other subjects and every subject is a method of learning other subjects. Analyzing the students’ ability to systemize knowledge obtained from different sources, we found that this ability is lagging behind the level that would be typical of the program. Often 5th-8th grade students don’t realize that that they have individual pieces of knowledge that are pertinent to each other just waiting to be connected. In our opinion, the reason lies in the very process of learning. The experimental material received during the teacher survey demonstrated their "disinterest" in students’ old knowledge, which is related to new. Programs and methodologies do not push teachers to go this direction. Therefore, we are often faced with the old knowledge being forgotten over time, and the overall excellence of students does not comply with the knowledge gained in previous classes. Students absorb new knowledge well and forget the old knowledge that is related to the new if that relationship is not pointed out. The absence of a connection between related new and old knowledge, i.e. the absence of "Problematic situations as higher reasoning," gives a formal nature to the knowledge obtained in class; the student does not fully understand the meaning of this knowledge and doesn’t systemize it.